Penegakan Hukum terhadap Jaksa yang Melakukan Tindak Pidana Narkotika - Wisnu Gita Prapanca; Suwari Akhmaddhian (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2019)
The purpose of this study is to find out how is the code of conduct for prosecutors in Indonesia? settlement of cases of violation of the Code of Ethics of the Prosecutor conducting Narcotics distribution? The research method used is normative juridical, which is an approach method by studying the law which is conceptualized as a norm or rule that applies in society, and serves as a reference for everyone's behavior. data collection tool through library research. ata used secondary, that is data obtained through the study of documentation by reading scientific books, magazines, internet, newspapers and other readings related to research. The results of the study are the setting of a prosecutor's code of ethics contained in Law Number 16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia and Regulation of the Attorney General of the Republic of Indonesia number: PER-067 / A / JA / 07/2007 concerning the Attorney Code of Ethics. Completion of cases of violations of the Code of Ethics for Prosecutors who commit violations of ethical conduct, namely examinations by the prosecuting supervisor and the type of severe punishment may be imposed on prosecutors in the form of dismissal with respect or vice versa with respect. In addition, the release from functional or structural positions.Keywords: sanctions; code of Ethics; prosecutor; case; judicial mafia.AbstrakTujuan penelitian ini adalah untuk mengetahui bagaimana bagaimana pengaturan kode etik bagi Jaksa di Indonesia? penyelesaian kasus pelanggaran  Kode Etik Jaksa yang melakukan pengedaran Narkotika? Metode penelitian yang digunakan adalah yuridis normatif, yaitu metode pendekatan dengan mengkaji hukum yang dikonsepkan sebagai norma atau kaidah yang berlaku dalam masyarakat, dan menjadi acuan perilaku setiap orang. alat pengumpul data melalui studi kepustakaan. ata yang digunakan sekunder, yaitu data yang diperoleh melalui studi dokumentasi dengan cara membaca buku-buku ilmiah, majalah, internet, surat kabar dan bacaan-bacaan lain yang berhubungan dengan penelitian. Hasil penelitian yaitu pengaturan kode etik jaksa terdapat dalam Undang-Undang Nomor 16 Tahun 2004 tentang Kejaksan Republik Indonesia dan Peraturan Jaksa Agung Republik Indonesia nomor : PER-067/A/JA/07/2007 tentang Kode Etik Jaksa. Penyelesaian kasus pelanggaran  Kode Etik Jaksa yang melakukan pelanggaran kose etik yaitu pemeriksaan oleh jaksa pengawas dan jenis hukuman berat dapat dikenakan terhadap jaksa berupa pemberhentian dengan tidak hormat atau sebaliknya dengan hormat. Selain itu pembebasan dari jabatan fungsional ataupun struktural.Kata Kunci : sanksi; kode etik; jaksa; perkara; mafia peradilan.